Lymphatic Filariasis - Goel, Trilok Chandra; Goel, Apul (Springer Nature Singapore : Imprint: Springer, 2016)
This book provides up-to-date information on lymphatic filariasis supported with abundant images, tables and algorithms. It is a first such monograph on a disease that has varied presentations which are complete clinical entities, such as chyluria, hydrocele, elephantiasis, etc. This book consists of three parts, parasitology, acute clinical manifestations and chronic presentations of the disease. Approximately 120 million people are infected with lymphatic filariasis in tropical and subtropical countries. About a third of these suffer clinical consequences of this infection, and many are seriously disfigured. India, Indonesia and Nigeria are the most endemic countries in the world. In spite of Global Control Program of WHO, filariasis continues to be a significant medical challenge and current efforts underway will take a long time to bring it under control. Lymphatic Filariasis is meant for general surgeons, physicians, urologists and plastic surgeons, including the postgraduate students. Useful for epidemiologists, internists, and those involved in filariasis prevention programs.